Efektifitas Penggunaan Metode Smart Energy (REIKI) Sebagai Alternatif Preventif Hyperglikemia Pasien Diabetes Melitus Tipe 2 - Aprilia Susanti; Dyah Rohmawati; Amik Muladi (Husada Mahakam, 2019)
DM affects many people in the world and is one of the biggest problems for the nation. Some treatments ranging from medical to non-medical (alternative actions) have been carried out by each individual to be able to recover from the disease. Alternative and complementary therapies are therapies that are in great demand by people throughout the world, not least in Indonesia because they are relatively cheap and safe. One alternative therapy that can be done is by the "Smart Energy" Method. Therefore, research on the use of the "Smart Energy" Method as a preventive alternative for reducing blood sugar levels in DM patients is very important. The purpose of this study was to find out and evaluate the effectiveness of using the "Smart Energy" Method as a preventive alternative for reducing blood sugar levels in DM patients. The design used in this study used a pre-experimental method with the one-group pretest-posttest design (before and after) approach. Each research subject becomes control of himself. The research was conducted at the DM Rehab Club. Taking blood samples as well as carrying out the therapy and evaluation is done on the same day. The duration of therapy is ± 20-30 minutes and carried out for 30 days with 2 methods namely direct therapy (therapist and respondent are in the same place) and long distance (therapist and respondent are not in the same place) but the principle of therapy remains the same. The implementation of Reiki therapy is assisted by a certified Reiki therapist. There was a significant difference between the examination of blood sugar levels before and after Reiki therapy. The average value of blood sugar levels before therapy is 294 mg / dl while after 30 days of therapy 266,635 mg / dl is obtained. There is effective use of the "Smart Energy" Method as a preventive alternative for reducing blood sugar levels in DM patients.